High-Sensitivity C - reactive protein As an Independent Predictor of Cardiovascular Complications in Chronic Obstructive Pulmonary Disease - Dr.Gaurav Dhandoria; Dr R P Meena; Dr Chitrak Jharwal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Systemic low-grade inflammation is believed to link chronic obstructive pulmonary disease (COPD) with excess cardiovascular (CV) morbidity. High-sensitivity C-reactive protein (hsCRP) is an inexpensive, stable biomarker of this inflammatory state, yet its prospective prognostic value in COPD is uncertain. Objective: To determine whether baseline hsCRP independently predicts incident composite CV events over 12 months in clinically stable COPD and to consider implications for emerging anti- inflammatory pharmacology and drug-safety monitoring. Methods: In a prespecified sub-study of our echocardiographic cohort, 126 consecutive out- patients (June 2016 – May 2019) with post-bronchodilator FEV₁/FVC < 0.70 and ≥ 6 weeks clinical stability were followed for 12 months. Baseline hsCRP was measured by immunonephelometry (Siemens BN II) and dichotomised at 3 mg L⁻¹. The primary end-point was first occurrence of composite CV events (non-fatal myocardial infarction, stroke/TIA, hospitalised heart failure or CV death) adjudicated by blinded cardiologists. Multivariable Cox regression adjusted for age, sex, pack-years, GOLD grade, hypertension, diabetes and ischaemic heart disease. Results: Median hsCRP was 3.8 mg L⁻¹ (IQR 2.1–6.2); 54 % of patients exceeded 3 mg L⁻¹. Twenty-six events occurred (event rate 21 %): heart-failure hospitalisation 12, non-fatal MI 7, stroke/TIA 4, CV death 3. Event incidence was 31 % in the high-hsCRP group versus 9 % when ≤ 3 mg L⁻¹ (p = 0.002). hsCRP > 3 mg L⁻¹ doubled risk (adjusted HR 2.12, 95 % CI 1.01–4.46; p = 0.047). Adding hsCRP to a clinical model improved the C-statistic from 0.70 to 0.77 (p = 0.03) and net re-classification index by 0.21. Conclusions: Baseline hsCRP > 3 mg L⁻¹ independently predicts short-term CV events in COPD. Routine inflammatory profiling could refine risk stratification and guide inclusion in anti- inflammatory drug trials.